The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1152/ajpgi.00098.2019
|View full text |Cite
|
Sign up to set email alerts
|

Enteroids expressing a disease-associated mutant of EpCAM are a model for congenital tufting enteropathy

Abstract: Congenital tufting enteropathy (CTE) is an autosomal recessive disease characterized by severe intestinal failure in infancy and mutations in the epithelial cell adhesion molecule ( EPCAM) gene. Previous studies of CTE in mice expressing mutant EpCAM show neonatal lethality. Hence, to study the cellular, molecular, and physiological alterations that result from EpCAM mutation, a tamoxifen-inducible mutant EpCAM enteroid model has been generated. The presence of mutant EpCAM in the model was confirmed at both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…A significant decrease in Paneth and goblet cell numbers in CTE patients and CTE mice has previously been reported [8]. In order to assess whether other secretory cells types are affected in CTE, we evaluated numbers of enteroendocrine cells in the CTE mice.…”
Section: Cte Mice Have Decreased Numbers Of Enteroendocrine Cells Andmentioning
confidence: 84%
See 2 more Smart Citations
“…A significant decrease in Paneth and goblet cell numbers in CTE patients and CTE mice has previously been reported [8]. In order to assess whether other secretory cells types are affected in CTE, we evaluated numbers of enteroendocrine cells in the CTE mice.…”
Section: Cte Mice Have Decreased Numbers Of Enteroendocrine Cells Andmentioning
confidence: 84%
“…Another study of adult mice bearing the same mutation revealed growth retardation, CTE-like histopathology, impaired intestinal barrier function and decreases in the tight junction proteins zonula occludens-1 (ZO-1) and occludin [7]. CTE intestinal organoids from mice reveal alterations in differentiation in addition to barrier dysfunction [8]. Moreover, data suggest that deficiency of EpCAM in a colonic cell line is accompanied by ion transport and barrier defects [7].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Reductions in the frequency and/or function of Paneth cells and intestinal epithelial cells in T2R mice were detected in vivo. CTE patients and mutant mice model had significantly fewer Paneth cells and goblet cells than their healthy counterparts [28]. However, forced expression of murine TROP2 in intestine was sufficient to support adequate Paneth cell numbers for survival in the absence of endogenous EpCAM.…”
Section: Discussionmentioning
confidence: 96%
“…However, for specialized secretory cells, challenged with mutated secretory proteins, UPR activation alone may not meet such demands. Indeed, the vulnerability of secretory cells to ER stress may account for the decreased numbers of Paneth and goblet cells seen in CTE patients and the CTE murine model [40]. Thus, alterations in mucosal homeostasis in CTE and models of the disease are likely due, at least in part, to aberrant expression of mutant EpCAM.…”
Section: Discussionmentioning
confidence: 99%